Carl Schmitt state and society - Rasch, William, 1949- (Rowman & Littlefield International, Ltd., 2019)
"William Rasch offers a reading of Carl Schmitt that avoids rehashing the controversies of the Weimar era in favour of examining a broader historical context. He examines Schmitt's notion of political theology, eschewing theocratic intention but taking seriously the 'secularization' of patterns of thought derived from Medieval theology"--